Application Status and Development Trend of Performance-Based Seismic Design Methods - Dong, Shuai; Liu, Yingli (Scientific Journal of Technology, 2025)
Performance based seismic design (PBSD) method is a frontier subject in the field of seismic engineering in recent years. Compared with the traditional code based design method, PBSD pays more attention to the actual performance of the structure under earthquake action. By discussing the application status and development trend of PBSD method, this paper summarizes its advantages in seismic engineering, and analyzes the comparison with traditional design methods. The results show that PBSD has significant advantages in improving the seismic performance of structures and reducing economic losses, but it also faces the challenges of technical complexity and practical application.